In Defense of Relational Direct Realism. (22nd March 2011) - Hobson, Kenneth
<x xml:space="preserve">Abstract</x> Abstract: According to proponents of relational direct realism, veridical perceptual experiences are irreducibly relational mental states that include as constituents perceived physical objects or intrinsic aspects of them. One consequence of the theory is the rejection of the causal theory of perception. This paper defends the relational theory against several objections recently developed by Paul Coates. He argues that the required experiential relation is incoherent and unmotivated. The argument that it is incoherent commits a fallacy. In reply to the argument that it is unmotivated, I suggest that the relational theorist's appeal to transparency provides sufficient motive and, when properly clarified, defeasibly justifies the theory as well. Coates also argues that rejection of the causal theory leaves relational theorists without any way of determining which object is perceived or of accommodating our scientific understanding of perceptual experiences as causally dependent on physical objects. I reply that relational theorists are able to provide the required explanations and discuss how the relational theory is consistent with this scientific understanding of perceptual experience.